Pengaruh Kegiatan Kolase Terhadap Kreativitas Pada Anak Usia 5-6 Tahun di TK GKPI Tarutung Kota Tahun Ajaran 2022/2023 - Rosinda Br Hotang; Emmi Silvia Herlina; Endang Junita Sinaga (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2023)
The aim of this research is to determine the effect of collage games on creativity in children aged 5-6 years at the GKPI Tarutung City Kindergarten. The method used in this research is a descriptive quantitative research method. The population is all GKPI Tarutung City Kindergarten children for the 2022-2023 academic year, totaling 130 people and a sample of 25 people was determined using a purposive sampling technique. Data was collected using 13 positive closed observation items. The results of data analysis show that there is an influence of collage games on creativity in children aged 5-6 years at GKPI Tarutung City Kindergarten: 1) Test analysis requirements: a) positive relationship test obtained by rxy = 0.613 > rtable(=0.05, n=25) = 0.396, thus it is known that there is a positive relationship between variable 2.069, thus there is a significant relationship between variable 0.67X. Thus Ha is accepted and H0 is rejected.